Development of PBL-Based Interactive Multimedia to Improve Learning Outcomes on Human Digestive System Material - Adiibah Asmaa Shofiyah; Aldina Eka Andriani (JURNAL PENDIDIKAN MIPA, 2026)
This research is based on the fact that teachers are not yet optimal in presenting technology-based learning media, resulting in low learning outcomes on the human digestive system material.This study aims to describe the development design, test the feasibility, and effectiveness of PBL-based Interactive Multimedia to improve learning outcomes of human digestive system material. The type of research is R&D with the ADDIE model including analysis, design, development, implementation, and evaluation. The research subjects were 20 fifth grade students. Data collection techniques were non-tests (observation, interviews, questionnaires, documentation) and tests (pre-test and post-test). Data analysis techniques were normality tests, t-tests, and N-Gain tests. The PBL-based interactive multimedia development design used Canva to design integrated PBL syntax starting with a video stimulus and equipped with simple experiments. The feasibility of interactive multimedia was shown by the results of the material validator of 91.07% and the media of 91.07% supported by the results of the analysis of teacher responses of 100% and students of 89.37% in the very feasible category. The effectiveness of PBL-based Interactive Multimedia is shown to increase learning outcomes by 24.28%, supported by the results of a significance analysis of 0.000 and an N-Gain of 0.631 in the moderate category. The conclusion of the study, PBL-based interactive multimedia on the human digestive system material was successfully developed, very feasible, and effective in improving the learning outcomes of fifth-grade students at SDN Karanganyar Gunung 01, Semarang City.